Cultural and Aesthetic factors in power plant design preferences - Shamsudin, Ahmad Faizul; Midden , Cees; Kaiser, Florian G. (Common Ground Publishing Pty Ltd, 2009)
The major facets of an aesthetic perspective from functions, aesthetic appeal, restoration, attraction, visual appeal and norms in current studies indicate a prospect of an environmental indicator with cultural notions. The field study measured both preferences and the combined facets of the aesthetic perspective separately for power plant designs in a natural environment. The environmental indicator or proposed as the culturally related aesthetics (CRA) are represented by preference predictors of beauty, order, pleasant, legible, logical and interesting. The results found a one-dimensional culturally related aesthetics (CRA) factor. It was also found to be related strongly to preferences of power plant designs. The implication is that the environmental indicator termed as culturally related aesthetics (CRA) can be integrated as a dimension to predict preferences for power plant designs. The intention is to fit well the huge structure of an industrial building with the local natural and cultural landscapes in the area.